Upper limit on the tau-neutrino mass. - Abachi, S; Akerlof, C; Baringer, P; Beltrami, I; Blockus, D; Bonvicini, G; Brabson, B; Bylsma, BG; Chapman, J; Cork, B; DeBonte, R; Derrick, M; et al. (1986)
A sample of lepton decays to 5± and 5±0 observed in the high-resolution spectrometer at the SLACe+e- storage ring PEP, has been used to place an upper limit on the mass of the tau neutrino of 84 MeV/c2 at the 95% confidence level. © 1986 The American Physical Society.